The reality of the role of guidance and educational media in Jordanian educational institutions - Al-Momani, Mohammad Omar (2022)
The study aimed to identify the reality of the role of guidance and educational media in Jordanian educational institutions. The descriptive approach was used in addition to the use of a questionnaire consisting of three areas by 10 paragraphs for each field as a tool for the study, which was applied to a sample of 400 male and female students. Among the students of the basic stage, it was concluded that educational media is witnessing a kind of effectiveness as it works to urge students to self-inquiry, and it is possible to discover and highlight the abilities and potentials of students, as it is possible to clarify the future prospects of study specializations in the labor market. It was also concluded that the effectiveness of educational media does not differ according to gender and method of guidance.